H7N9 live attenuated influenza vaccine in healthy adults: a randomised, double-blind, placebo-controlled, phase 1 trial. Issue 3 (March 2016) - Rudenko, Larisa; Isakova-Sivak, Irina; Naykhin, Anatoly; Kiseleva, Irina; Stukova, Marina; Erofeeva, Mariana; Korenkov, Daniil; Matyushenko, Victoria; Sparrow, Erin; Kieny, Marie-Paule
Summary: Background: H7N9 avian influenza viruses characterised by high virulence and presence of mammalian adaptation markers have pandemic potential. Specific influenza vaccines remain the main defence. We assessed the safety and immunogenicity of an H7N9 live attenuated influenza vaccine (LAIV) candidate in healthy adult volunteers. Methods: We did a phase 1, double-blind, randomised, placebo-controlled trial in Saint Petersburg, Russia. Eligible participants were healthy adults aged 18–49 years. The participants were randomised 3:1 to receive live vaccine or placebo, according to a computer-generated randomisation scheme. Two doses of vaccine or placebo were administered intranasally 28 days apart, each followed by 7 day stays in hospital. Immune responses were assessed in nasal swabs, saliva, and serum specimens collected before and 28 days after each vaccine dose. The primary outcome was the safety profile. This trial is registered withClinicalTrials.gov, numberNCT02480101 . Findings: Between Oct 21, 2014, and Oct 31, 2014, 40 adults were randomised, of whom 39 (98%) were included in the per-protocol analysis (29 in the vaccine group and ten in the placebo group). The frequency of adverse events did not differ between the vaccine and placebo groups. Seroconversion of neutralising antibodies was seen in 14 participants after the first vaccine dose (48%, 95% CI 29·4–67·5) and 21 after the second vaccine dose (72%, 52·8–87·3). Immune responses were seen in 27 of 29 recipients (93%, 95% CI 77·2–99·2). Adverse effects were seen in 19 (63%) vaccine recipients and nine (90%) placebo recipients after the first dose and in nine (31%) and four (40%), respectively, after the second dose. These effects were mainly local and all were mild. Interpretation: The H7N9 LAIV was well tolerated and safe and showed good immunogenicity. Funding: WHO.